Analisis Financial Distress Dengan Metode Altman, Springate, Zmijewski, Grover : (Pada Perusahaan Food and Beverages BEI 2020-2023) - Judi Suharsono; Khusnik Hudzafidah; Retno Lailatul Aisyah (CV. Ulil Albab Corp, 2025)
This study aims to examine and analyze financial distress using the Altman Z-Scrore, Springate, Zmijewski, and Grover methods to predict bankruptcy in food and beverages companies listed on the Indonesia Stock Exchange for the period 2020-2023 and compare the most effective methods in analyzing financial distress. This study uses a descriptive quantitative approach method which is research conducted to determine the independent variable either one or more variables aims to analyze the problem of the relationship between one or more variables without making comparisons or connecting with other variables. The results of research using the Altman Z-Scrore, Springate, Zmijewski, and Grover methods make the Company able to analyze the Company's financial performance to prevent bankruptcy and from this study can compare between the Altman Z-Scrore, Springate, Zmijewski, and Grover methods. From the comparison results between the Altman Z-Scrore, Springate, Zmijewski, and Grover methods, the Grover method is the most effective and accurate method in analyzing financial distress with an accuracy rate of 98.4375% and an error type of 1.5625%. That way, the use of the Grover method can be used as a reference to prevent bankruptcy